The Employment Effects of Nearly Doubling the Minimum Wage - The Case of Hungary - Gabor Kertesi; Janos Kollo (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2003)
The effect of minimum wages on employment has been a matter of debate for more than a decade. Apart from a few cases (Puerto Rico, Indonesia, Columbia) the empirical works analysed the aftermaths of minor increases in the minimum wage, and yielded mixed results. Hungary 2000-2002 provides a unique opportunity to look at the effects of an exceptionally large minimum wage hike in a relatively developed market economy. Unexpectedly, the country's right-wing government increased the statutory minimum by 96 per cent (XX per cent in real terms) in only two steps between December 2000 and January 2002. The paper looks at the short-run effects of the first hike (57 per cent). It finds that increasing the minimum wage significantly reduced employment in the small firm sector and adversely influenced the jobloss and job finding probabilities of low-wage workers. The effects appear to be stronger in low-wage segments of the market, and depressed regions, where the minimum wage bites deeper into the wage distribution.
Keywords: J3; P3; 330; minimum wage; transition